Answer: get it I guess
Step-by-step explanation:
Answer:
A 50% increase followed by a 33/1/3% decrease. = ? (1 + 0.5)*(1 - 0.3333333) = 1.5 * 0.666667 = 1. Result is same as original.
Answer: Hahahhahahaha
Explanation:
Ihwhwbwbajbwbausbw ahjw
We are given with two equations 2x − 3y = −1 and <span>11x − 9y = −13. The problem says that when the first equation is multiplied by -3 which results to -6x + 9y = 3, the sum of the resulting equation and the second one is equal to 5x = -10. We verify this: -6x + 11x = 5x while -9 y and 9 y cancels out. 3+-13 equals -10. Hence the total is really 5x = - 10.</span>